2020
DOI: 10.1371/journal.ppat.1008553
|View full text |Cite
|
Sign up to set email alerts
|

Irgm1-deficiency leads to myeloid dysfunction in colon lamina propria and susceptibility to the intestinal pathogen Citrobacter rodentium

Abstract: IRGM and its mouse orthologue Irgm1 are dynamin-like proteins that regulate vesicular remodeling, intracellular microbial killing, and pathogen immunity. IRGM dysfunction is linked to inflammatory bowel disease (IBD), and while it is thought that defective intracellular killing of microbes underscores IBD susceptibility, studies have yet to address how IRGM/ Irgm1 regulates immunity to microbes relevant to intestinal inflammation. Here we find that loss of Irgm1 confers marked susceptibility to Citrobacter rod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…In the current work, we also found that 2DG reversed the decreased T cell viability that was found to accompany Irgm1 -deficiency in T cells. Thus, our findings add to and reinforce a growing hypothetical structure suggesting that loss of Irgm1 triggers at least two related pathways: (1) altered mitochondrial metabolism drives cytokine production and apoptotic cell death 15 , 27 as demonstrated here, and (2) decreases in clearance of damaged mitochondria prompt mitochondrial DNA engagement of the TLR7 and/ or cGAS/STING pathways driving further cytokine production as shown recently elsewhere 16 , 19 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the current work, we also found that 2DG reversed the decreased T cell viability that was found to accompany Irgm1 -deficiency in T cells. Thus, our findings add to and reinforce a growing hypothetical structure suggesting that loss of Irgm1 triggers at least two related pathways: (1) altered mitochondrial metabolism drives cytokine production and apoptotic cell death 15 , 27 as demonstrated here, and (2) decreases in clearance of damaged mitochondria prompt mitochondrial DNA engagement of the TLR7 and/ or cGAS/STING pathways driving further cytokine production as shown recently elsewhere 16 , 19 .…”
Section: Discussionsupporting
confidence: 89%
“…Our data demonstrate that Th1 CD4 T cells lacking Irgm1 have decreased cell survival as well as deficient function of existing cells, which in combination may well lead to failure to suppress populations of inflammatory enteric bacteria. Along those lines, our recent work has indicated that Irgm1 -deficient mice are unable to control replication and spread of the enteric bacterium and IBD model, Citrobacter rodentium 27 . Our current results also demonstrate that Treg cells lacking Irgm1 have impaired regulatory function, which likely also contributes to inefficient suppression of intestinal inflammatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that H. pylori induces IRGM downregulation in a strain-dependant manner, IRGM polymorphisms and microbial suppression act synergistically to prevent xenophagic clearance [49]. The deletion or knockdown of the murine ortholog Irgm1 results in increased susceptibility to both intracellular and extracellular bacteria, including Citrobacter rodentium [50], S. typhimurium [9], Mycobacterium tuberculosis [12], Listeria monocytogenes [51], and C. trachomatis [52]. Numerous mechanisms for increased susceptibility in murine Irgm1 −/− models have been proposed: failure of monocyte maturation upon lamina propia infiltration and apoptosis [50], abolishment of macrophage movement and adhesion [9], and loss of intracellular bacterial restriction mechanisms [52].…”
Section: Irgm During Microbial Insultmentioning
confidence: 99%
“…The deletion or knockdown of the murine ortholog Irgm1 results in increased susceptibility to both intracellular and extracellular bacteria, including Citrobacter rodentium [50], S. typhimurium [9], Mycobacterium tuberculosis [12], Listeria monocytogenes [51], and C. trachomatis [52]. Numerous mechanisms for increased susceptibility in murine Irgm1 −/− models have been proposed: failure of monocyte maturation upon lamina propia infiltration and apoptosis [50], abolishment of macrophage movement and adhesion [9], and loss of intracellular bacterial restriction mechanisms [52]. In vitro models using M. leprae and M. tuberculosis corroborate murine models, identifying increased IRGM expression upon infection [12,53].…”
Section: Irgm During Microbial Insultmentioning
confidence: 99%